Microstructure Control and Hot Cracking Prevention During Laser Additive Manufacturing of Cobalt-Based Superalloy - Xuanyu Liu; Xianghui Xiao; Wenjia Xiao; Junbin Zeng; Kuanfang He; Hui Xiao (Crystals)
Hot cracking is a frequent and severe defect that occurs during laser additive manufacturing of superalloys. In this work, a pulsed-wave (PW) laser modulation process was employed to control the solidification microstructure and reduce the hot cracking susceptibility of laser additive manufactured cobalt-based superalloy. The effects of continuous-wave (CW) and PW laser processing modes on the dendrite morphology, element segregation, eutectic phase, and hot cracking of fabricated Co-based superalloys were investigated. Optical microscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy were used to characterize the microstructural characteristics of samples. A two-color pyrometer was used to measure the molten pool temperature variation under different laser processing modes. The results show that coarse columnar dendrites, chain-like eutectic carbides, and hot cracks were observed in the CW sample. In contrast, the fine equiaxed crystals, discrete eutectic carbides, and low-level residual stresses were obtained to avoid hot cracks, owing to the high cooling rate and the periodic melting and solidification of the molten pool under the PW laser processing mode. This work provides a new method for controlling solidification structure and hot cracking of laser additive manufactured Co-based superalloy.